Traditional Yoga And Meditation Counseling As Non-Pharmacological Therapy For Insomnia In The Yoga Dhsp Bali Community, Banjar Singin, Selemadeg, Tabanan Regency - Putu Setiani; Agung Setiabudi; Anak Agung Dwi Ratih Arningsih; I Gede Eka Agung Agastya Punia; Made Adit Darma Putra (International Journal Labs, 2025)
Insomnia is a sleep disorder characterized by difficulty falling asleep or staying asleep. The causative factors can be related to stress, anxiety, irregular lifestyles, as well as certain medical conditions. Yoga is a physical, mental, and spiritual practice that has a variety of techniques, including posture (asana), breathing (pranayama), and meditation. The practice of yoga can help reduce stress and promote relaxation, which is important for overcoming insomnia. Yoga and meditation provide benefits such as improving sleep quality, reducing anxiety and stress, increasing awareness of the body, and improving emotional balance. Yoga and meditation should be considered as complementary to other approaches in the treatment of insomnia, such as lifestyle changes, stress management, and if necessary, the use of therapy or medical treatment. To get the maximum benefits, it is important to practice yoga and meditation regularly. This can be done by scheduling a specific time each day to practice. This counselling aims to increase public understanding of the importance of doing yoga and traditional meditation regularly as an alternative solution to the problem of insomnia sleep disorder